2019
DOI: 10.3390/app9061164
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal Shift of Tetrao urogallus in an Alpine Natura 2000 Site: Implications for Habitat Restoration

Abstract: Capercaillie (Tetrao urogallus L.), a territorial galliform species, is known to prefer mature conifer stands with canopy gaps and a vigorous understory of ericaceous species. Capercaillie is a useful umbrella species that has recently shown declining population trends and distribution changes in its southern geographic range. We aim to identify and assess the possible changes in summer capercaillie habitat selection between 2001 and 2011 in the Scanuppia Natura 2000 site (south-eastern Alps). The area is domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The behavioural thermoregulation hypothesis holds that animals can buffer the effects of climate change through behavioural regulation of body temperature and has already been observed in both ectotherms and endotherms (Chapperon & Seuront, 2011; Kearney et al, 2009). It is well known that a large number of alpine species are altitudinal migrants in accordance with habitat temperature changes in different seasons (Guan et al, 2013; Sitzia et al, 2019; Zeng et al, 2010). The primary response to climate warming of alpine species is upslope shifts (White et al, 2018), but continuous warming may lead to mountaintop extinctions of species whose ranges are confined to higher altitudes (Freeman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavioural thermoregulation hypothesis holds that animals can buffer the effects of climate change through behavioural regulation of body temperature and has already been observed in both ectotherms and endotherms (Chapperon & Seuront, 2011; Kearney et al, 2009). It is well known that a large number of alpine species are altitudinal migrants in accordance with habitat temperature changes in different seasons (Guan et al, 2013; Sitzia et al, 2019; Zeng et al, 2010). The primary response to climate warming of alpine species is upslope shifts (White et al, 2018), but continuous warming may lead to mountaintop extinctions of species whose ranges are confined to higher altitudes (Freeman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Current research confirms that high ambient temperatures strongly influence the activity of ungulates (du Toit & Yetman, 2005; Owen‐Smith & Goodall, 2014). A primary response of animals is to shift their range to cooler environments, generally by moving along thermal axes to higher elevations, higher latitudes or deeper water (Sitzia et al, 2019; Spence & Tingley, 2020). As the climate warms, the suitable summer habitat of alpine ungulates decreases and they migrate to higher altitudes, while suitable winter habitat may increase (White et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Landscape change is also affecting landscape perception by tourists (Pastorella et al, 2017) and different ecosystem services (Tattoni et al, 2021). The study of this phenomenon is important not only to assess its current impact on the ecological functionality of forest ecosystems, including biodiversity conservation (Sitzia et al, 2017) and protection against natural hazards (Sitzia et al, 2019), but also to build future scenarios, taking into account also climate change issues (Tappeiner et al, 2008). The limit of the mountain treeline is gradually shifting upwards and the monitoring and modeling of these changes will be crucial to plan future interventions and the implementation of effective adpatation measures (Cantiani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the public incentives to mow the grasslands in order to keep those habitats free from newborn trees, those measures were not effective everywhere, and the afforestation trend is generally still ongoing [8]. Forests are also growing at higher elevation both due to climate change and due to land abandonment, thereby invading the typical alpine grasslands [9]. Extensive agro-ecosystems, such as traditional mountain cattle breeding, are perceived positively by people because they are linked to historical traditions, familiar economies and traditional values [7] Schirpke et al, 2016 [10] reported that the demand for pleasant landscapes is an important topic for tourists in the alpine region, and several ecosystem services are linked to the complex structure of habitats that is perceived as a landscape.…”
Section: Introductionmentioning
confidence: 99%